Analysing team formations in football with the static qualitative trajectory calculus - Beernaerts, J.; Baets, B.; Lenoir, M.; Mey, K.; Weghe, N. (Proceedings of the 6th International Conference on Sport Sciences Research and Technology Support - Volume 1: icSPORTS, 2018)
In this paper, we introduce the Static Qualitative Trajectory Calculus (QTCS), a qualitative spatiotemporal method based on the Qualitative Trajectory Calculus (QTC), for team formation analysis in football. While methods for team formation analysis are mostly quantitative, QTCS enables the comparison of team formations by describing the relative positions between players in a qualitative manner, which is much more related to the way players position themselves on the field. To illustrate the method, we present a series of examples based on real football matches of a 2016-2017 European football competition. With QTCS, team formations of both an entire team as well as a smaller group of players can be described. Analysis of these formations can be done for multiple matches, thereby defining the playing style of a team, or at critical moments during a game, such as set pieces.